Re-Survey of Eighteen Community Development Blocks - Notes & Tables - Planning Commission (Planning Commission, 1965)
In 1954-55, the 1.3.0. had conducted a Bench Mark Survey in 20 community development Blocks with a special focus on the position regarding acceptance of sponsored practices and certain aspects of the rural economy related to the development programme as at the time of the survey or for a given period immediately before it”. Data for 18 of those blocks were fully analysed and brought out in P.3,0. publications Nos. 12, 13, 16, 17, 21, 22, 23, 24 and 25 .The results of this survey (BLIS) provide the base-line of the economic and social conditions in those areas, as in 1954-55. It was in the same 18 development blocks that a repeat survey (BLIS) was conducted in 1959-60, Besides, an initial Bench-Bark Survey was also conducted in 1959-60 in another sot of 34 blocks selected with greater attention on sampling methods from a restricted universe of the blocks then existing, This report, however, does not deal with the results of this fresh BLIS enquiry.
Notes & Tables
Government of India